Because of Winn-Dixie - DiCamillo, Kate. (Cambridge, Mass. : Candlewick Press, 2000)
Ten-year-old India Opal Buloni describes her first summer in the town of Naomi, Florida, and all the good things that happen to her because of her big ugly dog Winn-Dixie.
Otterbein PL copy In Memory of Ed Meyers
1 3 4 6 7 9 10 11 13 17 18 19 20 21 25 26 27 29 31 32 33 34 35 36 39
Keywords: Dogs -- Fiction; City and town life -- Florida -- Fiction; Family -- Juvenile fiction; Florida -- Fiction